2011
DOI: 10.1158/1078-0432.ccr-10-2225
|View full text |Cite
|
Sign up to set email alerts
|

MEK-Independent Survival of B-RAFV600E Melanoma Cells Selected for Resistance to Apoptosis Induced by the RAF Inhibitor PLX4720

Abstract: Purpose: To examine mechanisms that determine long-term responses of B-RAF V600E melanoma cells to B-RAF inhibitors. Experimental Design: B-RAF V600E melanoma cells were exposed to the B-RAF inhibitor PLX4720 for prolonged periods to select for cells resistant to apoptosis induced by the inhibitor. The resultant cells were analyzed for activation of extracellular signal regulated kinase (ERK), MAP/ERK kinase (MEK), and Akt, and related signals. Their roles in survival of the cells were also examined.Results: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 36 publications
4
96
2
2
Order By: Relevance
“…Jiang and colleagues (36) reported that activation of the PI3K/AKT pathway accounts for, at least in part, the MEK-independent survival of the BRAFi-resistant melanoma cells. The increased PI3K/ AKT activation is the result of extracellular stimuli in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and colleagues (36) reported that activation of the PI3K/AKT pathway accounts for, at least in part, the MEK-independent survival of the BRAFi-resistant melanoma cells. The increased PI3K/ AKT activation is the result of extracellular stimuli in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…BRAFi-resistant melanoma cells often exhibit crossresistance to other BRAF/MAPK pathway inhibitors such as drugs targeting MEK (44,59,60), suggesting that aberrant activity of other signaling pathways and cellular processes can compensate for the loss of BRAF/MAPK signaling. Indeed, many studies have observed increased activity of key mitogenic signaling proteins such as RTKs and AKT in BRAFi-resistant melanomas (9,14,15,47), while other studies report that BRAFi-resistant melanoma cells inactivate apoptotic pathways through downregulation of BIM (16) and upregulation of MDM4, a negative regulator of TP53 (18).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that BRAF mutant colorectal cancer COLO206F cells with acquired resistance to the AZD-6244 MEK inhibitor (COLO206F-AR) displayed 10 to 15 copies of mutant BRAF (8). We treated COLO206F parental and COLO206F-AR MEK-resistant cells with the 2 MEK inhibitors, the ERK inhibitor and the BRAF inhibitor PLX4720 (34). We found that, in contrast to MEK and BRAF inhibitors, the ERK inhibitor again largely maintained its ability to block proliferation and pathway suppression at the level of pRSK in the BRAF-amplified COLO206F-AR cells, with only an approximately 4-fold shift in sensitivity to ERKi relative to parental cells compared with a 125- to 150-fold shift in sensitivity to the 2 MEK inhibitors ( Fig.…”
Section: Meki-1 Erkimentioning
confidence: 99%